Prevalence of malnutrition and associated factors affecting the nutritional status of Adivasi (tribal) children aged 24-59 months in Bangladesh - Kabir, Md Ruhul; Rahman, Mostafizur; Mamun, Md Abdullah Al; Islam, Homayra (Asian Journal of Medical and Biological Research, 2018)
Despite of recent progress in reducing the incidence of child malnutrition in Bangladesh, there are large disparities exists across gender, geographical regions, ethnic and economic groups. Adivasi‟s (tribal people) are regarded as one of the most exploited and deprived section of the society and their children are one of the worst victims of under-nutrition. This study aimed to estimate the prevalence and associated factors of malnutrition in different tribal children aged 24-59 months. Data was extracted from a project named “Adivasi Fisheries Project (AFP)” and the study considered 125 children from four purposively selected household (HH) clusters of four ethnic groups (Santal, Garo, Oraon, and Hajong) by quota-sampling design using the farmer field school (FFS) as the sampling frame. Malnutrition status was determined by measuring underweight, stunting and wasting and the associations between variables and malnutrition status were found out. Regression analysis then confirmed the contributions of risk factors. The prevalence of underweight, stunting and wasting was 28%, 42% and 13% respectively. Malnutrition was found to be higher among Hajong and Oraon compared to Santal and Garo. Significant association was observed between family income and malnutrition status. Having a family income below 4000 BDT (~$50) significantly increased the risk for underweight, stunting and wasting. Moreover, younger mother‟s (age < 20 years) was more prone to have underweight and wasted children than their older counterparts. The study pinpointed that the standard of living of adivasi (tribal) people need to be improved and socio-demographic issues need to be addressed to tackle the malnutrition status of their children. Asian J. Med. Biol. Res. June 2018, 4(2): 178-185